Disregarding the voters?: Electoral competition and the Merkel government’s public policies, 2013-17 - Engler, Fabian; Bauer-Blaschkowski, Svenja; Zohlnhöfer, Reimut (German politics, 2019)
How did electoral competition during the second grand coalition under Chancellor Angela Merkel affect policy-making? By examining opinion polls and the outcomes of Länder elections, the article shows that on the demand side party competition was (potentially) intense. On the supply side, it discusses the major opposition parties’ policy positions and reviews whether the voters regarded them as credible and competent. Then it assesses the effects of this actor constellation for the two most salient policy areas, the euro crisis and the refugee crisis. It finds that the grand coalition partially revoked its initially liberal migration policy as the AfD gained strength and became a credible alternative for CDU/CSU (as well as SPD) voters. In contrast, euro rescue policy was largely unaffected by party competition because the issue was less salient and the CDU/CSU was regarded as the most credible party in this respect.